2021
DOI: 10.1021/acs.jpcb.1c00147
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and Temperature Dependence of Local Structure and Dynamics in an Ionic Liquid

Abstract: A detailed understanding of the local dynamics in ionic liquids remains an important aspect in the design of new ionic liquids as advanced functional fluids. Here, we use small-angle X-ray scattering and quasi-elastic neutron spectroscopy to investigate the local structure and dynamics in a model ionic liquid as a function of temperature and pressure, with a particular focus on state points ( P , T ) where the macroscopic dynamics, i.e., conductivity, is the same. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 58 publications
(116 reference statements)
0
24
0
Order By: Relevance
“…For ionic liquids QENS has revealed a complex picture of the dynamics with several different processes contributing to the local dynamics. [27][28][29][30][31][32] However, to the best of our knowledge no studies have been reported on the local dynamics in highly concentrated electrolytes using QENS.…”
Section: Introductionmentioning
confidence: 99%
“…For ionic liquids QENS has revealed a complex picture of the dynamics with several different processes contributing to the local dynamics. [27][28][29][30][31][32] However, to the best of our knowledge no studies have been reported on the local dynamics in highly concentrated electrolytes using QENS.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental works and computational modeling cover a range of temperatures of possible operating conditions between the melting and boiling points of the IL. 15 20 Studies on pressure effects on ILs focus mainly on structural and conformational changes or glass transitions, 21 31 but there are also several works investigating transport properties—diffusion coefficients or conductivity. 21 , 26 , 32 35 …”
Section: Introductionmentioning
confidence: 99%
“…In search of optimized electrolytes, ionic liquids (ILs) gained significant attention, owing to their several advantages, such as stability and nonvolatility. Experimental works and computational modeling cover a range of temperatures of possible operating conditions between the melting and boiling points of the IL. Studies on pressure effects on ILs focus mainly on structural and conformational changes or glass transitions, but there are also several works investigating transport propertiesdiffusion coefficients or conductivity. ,, …”
Section: Introductionmentioning
confidence: 99%
“…A three‐fold jump model is usually applied for the rotation of methyl groups in the cation [13,29] . The random jump model describes the intramolecular rotation of alkyl side chain of imidazolium cation [13] or pyrrolidinium cation [30] . Another model describes diffusive motion within a restricted space, like the vibrational motion of cation rings [13,30] or the localized confinement [7d] .…”
Section: Resultsmentioning
confidence: 99%
“…The random jump model describes the intramolecular rotation of alkyl side chain of imidazolium cation [13] or pyrrolidinium cation [30] . Another model describes diffusive motion within a restricted space, like the vibrational motion of cation rings [13,30] or the localized confinement [7d] . We will use this last model which captures the cation diffusion inside a confined sphere with radius a using the Equation: [21a,29a,31] truenormalEnormalInormalSnormalF=c1+(1-c1)(3j1()QaQa)2 …”
Section: Resultsmentioning
confidence: 99%